2021
DOI: 10.1002/aesr.202100005
|View full text |Cite
|
Sign up to set email alerts
|

Review on Polymeric, Inorganic, and Composite Materials for Air Filters: From Processing to Properties

Abstract: Particulate and gaseous air pollutants pose a threat to human health and contribute to climate change. By today, air filters, stationary and portable, are markedly improved and can often provide innocuous air pollution levels. After introducing the classification and standards on air filters, the influence of the processing route and its parameters on the resulting air filter properties and consequently its performance are discussed. Numerous tools are presented to adjust structural properties such as fiber or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 222 publications
(374 reference statements)
1
21
0
Order By: Relevance
“…An environmental study has shown that prolonged exposure to these particles increases mortality due to COVID-19. In fact, particles with high surface-to-volume ratios can absorb the virus-containing SARS-CoV-2 and spread viral infection [ [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An environmental study has shown that prolonged exposure to these particles increases mortality due to COVID-19. In fact, particles with high surface-to-volume ratios can absorb the virus-containing SARS-CoV-2 and spread viral infection [ [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…2 ). For gaseous pollutants, it is based on physisorption (based on weak Vander Waals force), and chemisorption (strong connection among pollutant and the filter material) [ 12 , [14] , [15] , [16] ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic fibers are formed by pyrolysis of an organic template fiber, which is then soaked in preceramic precursor materials, or precursor materials are deposited on its surface. A direct process involves the direct spinning of inorganic precursors (solutions of salt, suns, or molten precursors) into "green fibers", sometimes using organic polymer additives [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Producing HEPA filters requires relatively advanced fabrication technologies, 39 with a large proportion made of either glass fibers or plastics, the former of which requires an energy-intensive fabrication process, and the latter of which relies heavily on the petrochemical industries. 39,40 In addition, over time, a filter cake builds up on the fibers of the filter, resulting in increased resistance to airflow and the imminent need to replace the whole filter, with very limited options of cleaning and/or reuse. 40 Indeed, using HEPA filters on a global scale to combat the transmission of airborne viruses in indoor spaces incur prohibitive environmental and financial costs.…”
mentioning
confidence: 99%